RELIGIOSITY IN CRIMINAL LAW: ISLAMIC PERSPECTIVE - Abdurrahman Raden Aji Haqqi (Diponegoro Law Review, 2019)
The fundamental premises of Islamic law are that Allah has revealed His will for human-kind in the Holy Quran and the inspired example of the Prophet Muhammad (Peace be Upon Him), and that society's law must conform to Allah's revealed will. The scope of Islamic law is broader than the common law or civil law. In addition to core legal doctrines covering the family, wrongs, procedure, and commercial transactions, Islamic law also includes detailed rules regulating religious ritual and social etiquette. In Islam, religiosity is not asceticism in monasteries nor is it chattering from the pulpits. Instead, it is behaving in a manner that is requested from the Creator under all circumstances, places and times, in belief, statement and actions. Historically, law and religion have never been completely separated. They have never been so independent as to achieve complete autonomy from each other. Religion has essentially been embodied in legal systems, even in those that have aspired to privatize religion. Based on this fact, this paper discusses such fact i.e religiosity on specific theme of Islamic law that is criminal law which means the body of law dealing with wrongs that are punishable in Islamic law with the object of deterrence.